2013
DOI: 10.1002/cbin.10198
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of human adipose mesenchymal stem cells isolated from healthy and cancer affected people and their interactions with human breast cancer cell line MCF‐7 in vitro

Abstract: Adipose tissue is an attractive source of mesenchymal stem/stromal cells (MSCs) with potential applications in reconstructive plastic surgery and regenerative medicine. The aim of this study was to characterise human adipose tissue MSCs (ASCs) derived from healthy individuals and cancer patients and to compare their interactions with tumour cells. ASCs were isolated from adipose tissue of healthy donors, breast cancer-adjacent adipose tissue of breast cancer patients and tumour-adjacent adipose tissue of non-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…The pellets were resuspended in lysis buffer (154 mM NH 4 Cl) and incubated at room temperature for 10 min to lyse erythrocytes. Cells were seeded and cultured in 25 cm 2 culture flask in GM under standard conditions until colonies appeared (Trivanović et al, 2014).…”
Section: Isolation Expansion and Cultivation Of Mscsmentioning
confidence: 99%
“…The pellets were resuspended in lysis buffer (154 mM NH 4 Cl) and incubated at room temperature for 10 min to lyse erythrocytes. Cells were seeded and cultured in 25 cm 2 culture flask in GM under standard conditions until colonies appeared (Trivanović et al, 2014).…”
Section: Isolation Expansion and Cultivation Of Mscsmentioning
confidence: 99%
“…Other authors have reported that ASCs may be protective, particularly in suppressing tumor growth and stimulating apoptosis. Most of the articles reviewed consistently pointed out that the role of ASCs in tumor development is complex, and that the tumor microenvironment milieu in which ASCs are present and the mechanisms by which they migrate may influence their role in cancer development (41)(42)(43)(44)(45).…”
Section: Complex Nature Of Ascs In Tumor Behaviormentioning
confidence: 99%
“…Several mechanisms linking ASCs and tumor development/ progression have been described, with many studies highlighting the importance of tumor environment modification by ASCs (41)(42)(43)(44). ASCs may play a role in the creation of an inflammatory tumor microenvironment, which promotes tumorigenic activity.…”
Section: Ascs Influence the Tumor Microenvironmentmentioning
confidence: 99%
“…For the same reasons, MSCs have received great attention in cancer research. It has been proposed that normal MSCs (N-MSCs) and tumor MSCs (T-MSCs), although sharing similar phenotype properties, could have different influence on tumor development, demonstrating supportive role of T-MSCs in tumor growth [43, 44]. Aforementioned data indicated conspicuous importance of TME not only in tumor development, but also in cancer recurrence and poor prognosis of patients.…”
Section: Mscs: Recruitment and Functions In Tmementioning
confidence: 99%